Figurative Language in the Short Story Ayah by Tetin Sobariah on Kompas.id - SANTUSO, Santuso; TALLAPESSY, Albert (Integration: Journal Of Social Sciences And Culture, 2024)
Purpose:Literary works aim to entertain and hold aesthetic value. To achieve both, a literary work must be rich in the use of figurative language. This research aims to describe the use of figurative language in the short story Ayah by Tetin Sobariah.Methodology:This study is classified as qualitative descriptive research. The research data consists of words containing figurative language, sourced from Kompas.id. Data collection involves reading, note-taking, and classification techniques. Data analysis employs contemporary stylistic theory.Findings:The results of this research indicate that the short story Ayah exhibits various figurative languages, including the comparison style group (27 instances), emphasis style (20 instances), conflicting style (2 instances), and satirical style (1 instance). Other variations of figurative language identified include the certainty style (8 instances), causality style (7 instances), reinforcement style (6 instances), surprise style (3 instances), denial style (3 instances), and non-standard style (2 instances).Implication:This research enhances stylistic studies in understanding the role of figurative language in short stories. The findings can serve as a reference for language and literature learning. Additionally, it provides insights for writers to align their writing style with the characteristics of short stories in Kompas.id. Further research may reveal patterns of figurative language usage and the literary identity of the media.